Oncologic outcomes of selective neck dissection in HPV‐related oropharyngeal squamous cell carcinoma. (16th September 2016) - Zenga, Joseph; Jackson, Ryan S.; Graboyes, Evan M.; Sinha, Parul; Lindberg, Miranda; Martin, Eliot J.; Ma, Daniel; Thorstad, Wade L.; Rich, Jason T.; Moore, Eric J.; Haughey, Bruce H.
Abstract : Objectives: To examine outcomes of selective neck dissection (SND) in patients with human papillomavirus (HPV)‐related oropharyngeal squamous cell carcinoma (OPSCC) who present with clinical neck disease. Study Design: Multi‐institutional retrospective review. Methods: Two institutional databases of patients with HPV‐related OPSCC were reviewed to identify patients with clinical (c) N1‐N3 neck disease who underwent SND ± adjuvant therapy. Results: Three hundred and twenty‐four patients were identified with a median follow‐up of 49 months (range 3–199 months). All patients underwent transoral resection of the primary tumor and SND, including levels II–IV and ± levels I or V, with resection of additional nonlymphatic tissue (extended SND) as indicated by extent of disease, including the spinal accessory nerve (7%), the internal jugular vein (13%), and the sternocleidomastoid muscle (8%). Two hundred and seventy (83%) patients underwent adjuvant radiation. There were 13 (4%) regional recurrences and 19 (6%) distant recurrences. Regional control following salvage was 98%. On univariable analysis, absence of radiation was associated with regional recurrence (odds ratio [OR] 9.2, 95% confidence interval [CI] 2.9–29.4). On multivariable analysis, adjuvant radiation was associated with improved disease‐free survival (DFS) (OR 0.27, 95% CI 0.14–0.53) but lost significance for overall (OS) and disease‐specific survival (DSS) ( P > 0.05). Five‐year Kaplan‐Meier estimates for OS, DSS, and DFS were 88% (95% CI 84%–92%), 93% (95% CI 89%–96%), and 83% (95% CI 78%–87%), respectively. Conclusion: In HPV‐related OPSCC presenting with clinical neck disease, a SND ± additional tissue resection and adjuvant therapy, when indicated, provides excellent long‐term regional control. Omission of radiotherapy increases the risk of regional recurrence, although it may not significantly impact OS or DSS. It appears unnecessary to routinely perform a comprehensive neck dissection. Level of Evidence: 4. Laryngoscope, 127:623–630, 2017